Resurrection : The Origin and Goal of the Christian Life - Matera, Frank J. (Book collections on Project MUSE., 2015)
At the heart of the Christian message stands the proclamation of the resurrection: the good news that God raised Jesus from the dead. In Resurrection: The Origin and Goal of the Christian Life, Frank Matera explains why the resurrection was so important to the early church and why it remains important for Christians today. Beginning with the gospels, then moving to the Acts of the Apostles, the Pauline Epistles, and concluding with Hebrews, 1 Peter, 1 John, and the book of Revelation, Matera provides a comprehensive overview of how the different writings of the New Testament proclaimed the resurrection of Jesus Christ. Written in a clear and accessible manner, Matera presents readers with a way to understand the central message of the New Testament and of Christian faith: God raised Jesus from the dead. Building on this message, he shows that the resurrection of Jesus enables and empowers believers to live in the world today and provides them with the assurance that God will raise them from the dead as well.